Factors influencing taper failure of modular revision hip stems. (April 2018) - Krull, A.; Morlock, M.M.; Bishop, N.E.
Highlights: Simple stress analysis demonstrates the limited mechanical safety factor at the stem taper junction of modular hip revision systems, indicating that patient loading due to activity and/or weight should be limited. Increasing the taper junction diameter increases strength - but contact analysis demonstrated an increase in the risk of total surface damage unless the outer diameter is also increased. Contact analysis demonstrated that increasing the assembly force decreases the total surface damage but local magnitudes can still be critical. Abstract: Stem modularity of revision hip implant systems offers the advantage of the restoration of individual patient geometry but introduces additional interfaces, which are subjected to repetitive bending loading and have a propensity for fretting corrosion. The male stem taper is the weakest part of the modular junction due to its reduced cross section compared to the outside diameter of the stem. Taper fractures can be the consequence of overloading in combination with corrosion. The purpose of this study was to assess the influence of implant design factors, patient factors, and surgical factors on the risk of taper failure of the modular junction of revision stems. An analytical bending model was used to estimate the strength of the taper connection for pristine, fatigued and corroded conditions. Additionally, a finite element contact model of the taper connection was developed to assess the relative motion and potential for surface damage at the taper interface under physiological loading for varyied assembly and design parameters. Increasing the male taper diameter was shown to be the most effective means for increasing taper strength but would require a concurrent increase in the outer implant diameter to limit a greater risk of total surface damage for a thinner female taper wall. Increasing the assembly force decreases the total surface damage but not local magnitudes, which are probably responsible for crack initiation. It is suggested that in unfavourable loading conditions a monobloc implant system will reduce the risk of failure.